Three-Dimensional Human Neural Stem Cell Models to Mimic Heparan Sulfate Proteoglycans and the Neural Niche - Peall, Ian W.; Okolicsanyi, Rachel K.; Griffiths, Lyn R.; Haupt, Larisa M. (Seminars in Thrombosis and Hemostasis, 2021)
Heparan sulfate proteoglycans (HSPGs) are a diverse family of polysaccharides, consisting of a core protein with glycosaminoglycan (GAG) side chains attached. The heterogeneous GAG side-chain carbohydrates consist of repeating disaccharides, with each side chain possessing a specific sulfation pattern. It is the variable sulfation pattern that allows HSPGs to interact with numerous ligands including growth factors, cytokines, chemokines, morphogens, extracellular matrix (ECM) glycoproteins, collagens, enzymes, and lipases. HSPGs are classified according to their localization within an individual cell, and include the membrane bound syndecans (SDCs) and glypicans (GPCs), with perlecan, agrin, and type-XVIII collagen secreted into the ECM. The stem cell niche is defined as the environment that circumscribes stem cells when they are in their naïve state, and includes the ECM, which provides a complex contribution to various biological processes during development and throughout life. These contributions include facilitating cell adhesion, proliferation, migration, differentiation, specification, and cell survival. In contrast, HSPGs play an anticoagulant role in thrombosis through being present on the luminal surface of cells, while also playing roles in the stimulation and inhibition of angiogenesis, highlighting their varied and systemic roles in cellular control. To fully understand the complexities of cell-cell and cell–matrix interactions, three-dimensional (3D) models such as hydrogels offer researchers exciting opportunities, such as controllable 3D in vitro environments, that more readily mimic the in vivo/in situ microenvironment. This review examines our current knowledge of HSPGs in the stem cell niche, human stem cell models, and their role in the development of 3D models that mimic the in vivo neural ECM.
Keywords: HSPGs; neurogenesis; neural ECM; 3D tissue culture; stem cell therapy